Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 9 - Section 9.3 - The Parabola - Exercise Set - Page 997: 29



Work Step by Step

General form of a horizontal parabola is given as: $(y-k)^2=4p(x-h)$...(1) Here, $\text{Vertex}=(h,k)$ and focus is: $(h+p, k)$ General form of a vertical parabola is given as: $(x-h)^2=4p(y-k)$...(2) Here, $\text{Vertex}=(h,k)$ and focus is: $(h, k+p)$ As we are given focus: $(-3,4)$ Thus, from both forms of a parabola , we have two equations$k-p=2$ and $k+p=4$ Add these two equations, we get: $k=3$ Thus, $p=4-k=4-3=1$ From equation (1), we have $(x-(-3))^2=4(1)(y-3)$ or, $(x+3)^2=4(y-3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.